2017
DOI: 10.1187/cbe.17-03-0055
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Effect of Team-Based Learning on Motivation and Learning: A Self-Determination Theory Perspective

Abstract: A quasi-experimental study tested the effect of lecture-based courses and team-based courses on students’ motivation and learning. The results show that students in general were more autonomously motivated and competent in the team-based courses, relative to the lecture-based courses, but also less amotivated and more externally regulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 96 publications
(111 reference statements)
2
35
1
Order By: Relevance
“…As leaders have a special role in fostering work engagement among their followers [53], team-level EL fosters a shared feeling of engagement in the entire team and fosters a positive psychological climate that eventually motivates individual team members to perform, learn and innovate. For instance, it has been found among students that team-based learning increased when they receive more feedback (competence support), collaborated more closely (relatedness support), and had greater responsibility (autonomy support) [54,55].…”
Section: Cross-level Effect Of Engaging Leadership At the Team Level mentioning
confidence: 99%
“…As leaders have a special role in fostering work engagement among their followers [53], team-level EL fosters a shared feeling of engagement in the entire team and fosters a positive psychological climate that eventually motivates individual team members to perform, learn and innovate. For instance, it has been found among students that team-based learning increased when they receive more feedback (competence support), collaborated more closely (relatedness support), and had greater responsibility (autonomy support) [54,55].…”
Section: Cross-level Effect Of Engaging Leadership At the Team Level mentioning
confidence: 99%
“…Blumenfeld, Kempler, and Kracjik (2006) report that college classrooms using active learning principles such as inquiry, authenticity, and collaboration are more likely to be intrinsically motivating to students. Jeno, Raaheim, Kristensen, Kristensen, Hole, Haugland, and Maeland (2017) showed that team-based learning increased intrinsic motivation and identified regulation and decreased amotivation compared with lecture-based instruction for college students. Similarly, Serrano-Cámara, Paredes-Velasco, Alcover, & Velazquez-Iturbide (2014) reported higher levels of intrinsic motivation for college freshmen involved in collaborative learning activities compared with lecture.…”
Section: Motivationmentioning
confidence: 99%
“…Many active learning techniques rely on students collaborating in small groups, either in or out of class. These techniques include Process Oriented Guided Inquiry Learning (POGIL; Thomas et al, 2008) and team-based learning (TBL; Jeno et al, 2017), possibly in the context of the flipped classroom (Baepler et al, 2014;Betihavas et al, 2016). While the benefits of small-group learning, especially for women (Lewis et al, 2016;Sullivan et al, 2018;Neill et al, 2019), have been documented, less attention has been paid to students who may feel their identities put them at a disadvantage in small groups.…”
Section: Example Commentsmentioning
confidence: 99%